2007
DOI: 10.1038/nsmb1211
|View full text |Cite
|
Sign up to set email alerts
|

Two different Argonaute complexes are required for siRNA generation and heterochromatin assembly in fission yeast

Abstract: The RNA-induced transcriptional silencing (RITS) complex, containing Ago1, Chp1, Tas3 and centromeric small interfering RNAs (siRNAs), is required for heterochromatic gene silencing at centromeres. Here, we identify a second fission yeast Argonaute complex (Argonaute siRNA chaperone, ARC), which contains, in addition to Ago1, two previously uncharacterized proteins, Arb1 and Arb2, both of which are required for histone H3 Lys9 (H3-K9) methylation, heterochromatin assembly and siRNA generation. Furthermore, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(156 citation statements)
references
References 45 publications
11
145
0
Order By: Relevance
“…Not applicable DNA elimination scnRNAs, siRNA Lee and Collins, 2006) N. crassa (2) Qde2* Not applicable Quelling siRNA (Catalanotto et al, 2002;Maiti et al, 2007) S. pombe (1) Ago1* Not applicable Heterochromatic silencing, hcRNA (Irvine et al, 2006;Buker et al, 2007) chromosome segregation…”
Section: Twi1mentioning
confidence: 99%
“…Not applicable DNA elimination scnRNAs, siRNA Lee and Collins, 2006) N. crassa (2) Qde2* Not applicable Quelling siRNA (Catalanotto et al, 2002;Maiti et al, 2007) S. pombe (1) Ago1* Not applicable Heterochromatic silencing, hcRNA (Irvine et al, 2006;Buker et al, 2007) chromosome segregation…”
Section: Twi1mentioning
confidence: 99%
“…However, by using the Conserved Domain Search service (CD-Search) (26,27), an Arb2 conserved domain was detected in the FAM172A protein sequence. Arb2 is required for histone H3 Lys9 (H3-K9) methylation, heterochromatin assembly and siRNA generation (28). Histone H3 lysine methylation is generally associated with either gene activation or repression depending on the site of methylation (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ago1 slicing activity is required for TGS (37). A recent study showed the presence of another Ago1 complex, named the argonaute siRNA chaperone (ARC), in S. pombe (38). Interestingly, the slicing activity of Ago1 in this complex is inhibited by a protein partner, Arb1.…”
Section: Molecular Interaction Network Centered On Argonaute Proteinmentioning
confidence: 99%